Effect of Kinema Flour on Qualitative Properties of Biscuit - Ray, Subhajit (Journal of Food Technology Research, 2022)
Kinema was prepared by using the pure culture of Bacillus subtilis by the laboratory and traditional method. Now both these two kinema were dried in a batch type of tray drier at (65-70)0C for (8-10) hours and prepared to a fine powder. The chemical analysis of kinema powder prepared by pure culture and traditional method was found as 6.79%, 21.45%, 42.91%, 4.84%, 24.01% and 7.218%, 20.624%, 41.99% and4.17%, 25.998% in terms of moisture content, fat, protein, total ash, and total carbohydrate respectively. Biscuit fortified at a level of 10% kinema flour powder of particle size 200 μm prepared by both methods showed increased thickness and increased volume. Protein, fat, total ash, moisture content, total carbohydrate, acid insoluble ash and acidity of extracted fat for kinema biscuits prepared by these two methods were found as 17.438%, 12.958%,1.377%, 4.94%, 63.287%, 0.234%, 0.501% and 17.157%, 12.458%, 1.045%, 5.00%, 64.344%, 0.248%, 0.422% respectively. Finally, kinema biscuits prepared by both these two methods showed better sensorial quality in comparison with a standard biscuit.